A new species of Spiroberotha Adams 1989 (Neuroptera: Berothidae) and the first record of the genus in Brazil - Machado, Renato Jose Pires; Krolow, Tiago Kütter (Zootaxa, 2016)
The genus Spiroberotha Adams, 1989 is classified in Berothidae (Neuroptera) with two described species: S. fernandezi Adams, 1989 from Venezuela and S. sanctarosae Adams, 1989 from Colombia, Costa Rica and Venezuela. Here we describe a new species, S. tocantinensis n. sp., from Palmas, Tocantins, Brazil. This is the first record of the genus in Brazil, extending its geographical distribution.